Virus Detection using Second Harmonics of Magnetic Nanoparticles. Issue 8 (12th April 2022) - Hirota, Ryuichi; Murayama, Toru; Katsumi, Ryota; Kawawaki, Tokuhisa; Yabukami, Shin; Igarashi, Ryuji; Negishi, Yuichi; Kusakabe, Moriaki; Sekino, Masaki; Yatsui, Takashi; Kuwahata, Akihiro
Abstract : Virus detection methods based on the nonlinear magnetic response of magnetic nanoparticles have been investigated, and magnetic detection methods using the third harmonic have been widely applied on account of their high sensitivity, short measurement‐time, and low cost. In this letter, we propose a virus detection method using the second harmonics to improve the signal intensity. We find that the signal to noise ratio of the second harmonic is approximately three times higher than that of the third harmonic. A comparison of the ratio of the second harmonic to the fourth harmonic ( R 24 ) and the ratio of the third harmonic to the fifth harmonic ( R 35 ) shows that R 24 is more sensitive to identifying changes in virus concentration. Our proposed method has the potential to be utilized for rapid screening on virus detection. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.